Dermoscopy of Cutaneous Graft-Versus-Host-Disease in Patients After Allogeneic Hematopoietic Stem Cell Transplantation - Grażyna Kaminska-Winciorek; Iris Zalaudek; Włodzimierz Mendrek; Magdalena Jaworska; Maksymilian Gajda; Jerzy Hołowiecki; Jan Szymszal; Sebastian Giebel (Adis, Springer Healthcare, 2020)
Abstract Introduction Progress in the transplant procedure has resulted in a higher proportion of patients with long-term survival after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Cutaneous graft-versus-host disease (GvHD) occurs often among patients who have undergone allo-HSCT. Routine diagnosis of skin and mucosal lesions is based primarily on clinical evaluation and histopathologic confirmation of skin biopsies. However, biopsy is an invasive method and histopathologic analysis is time-consuming, often accompanied by a lack of clinical correlation. There is therefore an urgent need for non-invasive, reproducible in vivo imaging methods that could be used in patients with cutaneous GvHD-both in the setting of initial diagnosis and during follow-up.The aim of the study reported here was to determine the role of dermoscopic monitoring of skin lesions in allo-HSCT recipients with consecutive histopathologic support as a non-invasive, alternative method to diagnose GvHD. Methods Twenty patients were examined by dermoscopy upon the manifestation of skin changes in the course of GvHD. Consecutive skin biopsies for histopathologic analysis were obtained from the suspected skin locations determined during dermoscopy. Results Graft-versus-host disease was confirmed by histopathology in 19 of the 20 allo-HSCT recipients. Four patients developed symptoms of acute cutaneous GvHD (grade 1, n = 2; grade 2, n = 1; grade 3, n = 1), and 15 patients developed chronic cutaneous GvHD. The most frequent dermoscopic signs (irrespective of whether GvHD was chronic or acute) were vessels and scaling (both n = 14, 73.7%). Hyperpigmentation and white patchy areas were present in eight patients (42.1%). Fair to moderate levels of agreement were found between presence of melanophages in the skin sample and dermoscopic granularity (Cohen's Kappa [κ] = 0.39), scaling (κ = − 0.3) and vessels (κ = − 0.42). The finding of white patchy areas was inversely associated with lymphocytic infiltration (κ = − 0.55). Conclusion The results of this study suggest that dermoscopy may be a useful tool for diagnosing cutaneous GvHD in allo-HSCT recipients. Combining the clinical picture with dermoscopic features may bring us closer to a faster and easier diagnosis of GvHD.